Perceptions of farmers regarding peatland restoration model of paludiculture in South Sumatra, Indonesia - Pusvita, Ema; Mulyana, Andy; Adriani, Dessy; Antoni, Mirza (Heritage and Sustainable Development, 2024)
Peatland fires are a common problem requiring urgent and comprehensive action. Therefore, this research aimed to examine perceptions of farmers regarding paludiculture model in peatland restoration efforts. The methodology used was a case-study design, while sampling was carried out with a deliberate method, producing a total of 50 farmers. Data analysis was performed through tabulation followed by interpretation using Likert tables. Statistical tests were conducted with chi-square, multiple linear regression, and logistic analysis. The results showed that perceptions of farmers were in a good category, with the influencing factors being social, economic, and environmental. Efforts made by the government and academics produced significant results regarding the factors influencing perceptions to adopt paludiculture model. Adopters were divided into five categories of farmers with the largest number being the initial majority, namely 23. Chi-square analysis identified variables strongly related to perceptions of farmers, including income, production amount, and education. The decision of farmers depends on the assessment of perceptions regarding the paludiculture model. In conclusion, the paludiculture model is a solution for making informed decisions to sustain peatland and yield significant profits for farmers.